ON THE ACTIVITIES OF ARZYMBET KAZY, THE PEOPLE'S JUDGE OF THE KUKUZYAK VOLOST - Opaev, Baymurat Abdreshitovich (SCIENCE and SOCIETY, 2026)
This article chronicles the life and socioeconomic activities of the renowned people's judge Arzymbet Qazi, who served in the Kukuzyak volost in the late 19th and early 20th centuries. It provides information on the judicial activities of Arzymbet Qazi and his efforts to improve the lives of his people.
Keywords: Arzymbet Qazy; Kukuzyak volost; people’s court; 19th century; early 20th century; colonial period; justice; governance; traditional court; Amudarya division; Chimbay district